Unilateral higher division of sciatic nerve and its clinical importance - Jandial, Sonia (International Journal of Research in Medical Sciences, 2019)
The sciatic nerve has a long course right from the pelvis to the apex of the popliteal fossa. The point of division of the sciatic nerve into tibial and common peroneal nerves is very variable. The variation in the division of the sciatic nerve described in the present study should be helpful for anaesthetists and orthopaedic surgeons. While doing the dissection and teaching of the gluteal region in the Post Graduate Department of Anatomy, government medical college, Jammu, it was found that on the left side tibial nerve and common peroneal nerve were present instead of sciatic nerve. It meant that the main nerve that is the sciatic nerve had already been divided into its terminal branches in the pelvis region. Both tibial and common peroneal nerve were seen coming out of the pelvis below the piriformis muscle, while on the right side there were no variation. The sciatic nerve was seen coming out of the pelvis below the piriformis muscle as usual. Because of this high division of the sciatic nerve in the pelvis, there are many complications like failed sciatic nerve block during anaesthesia while performing surgery, but high division of the sciatic nerve may result in escape of either tibial nerve or common peroneal nerve. The gluteal region, back of the thigh and leg of the lower limb were dissected to study further course of tibial nerve and the common peroneal nerve. Photographs were also taken.